Ku‐band pre‐matched broadband GaN power amplifier with over 30 W power. Issue 10 (1st May 2016) - Yuan, Ye; Fan, Yong; Chen, Zhe; Yang, Ziqiang; Lin, Haodong
Abstract : A Ku‐band pre‐matched broadband gallium nitride (GaN) power amplifier is proposed. Compared to conventional internally matched power amplifier, this high‐power amplifier (HPA) can provide broadband and high‐power gain. Measurement results show that the HPA has >20 dB power gain in the frequency range of 13.5–17 GHz. The maximum saturated output power ( P sat ) of 46 dBm and power added efficiency (PAE) of 42% are achieved at 15.5 GHz.